Chagas Disease - Basic Investigations and Challenges 2018
DOI: 10.5772/intechopen.77980
|View full text |Cite
|
Sign up to set email alerts
|

Chagas Cardiomyopathy: Role of Sustained Host-Parasite Interaction in Systemic Inflammatory Burden

Abstract: The economic and social burden associated with Chagas disease morbidity and mortality is regrettably large in Latin America causing more deaths than does any other parasitic disease. Inflammatory dilated cardiomyopathy is, by far, the most important clinical consequence of Trypanosoma cruzi infection. The insidious persistence of this parasite determines chronic myocarditis progression. The clinical outcome is multifactorial and depends on the particular parasite strain and virulence factors, the infective loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
1
2
0
1
Order By: Relevance
“…Interestingly, the myocarditis degree and HIF‐1α/CD73 expressions directly correlated with cardiac parasite load. These findings are consistent with works that report a positive correlation between the parasite persistence and the extension of inflammatory infiltrate in Chagas myocarditis 15,51,52,53,54 . Notably, Chagas patients have worse prognosis compared to cardiomyopathies from other etiologies and, in particular, male gender has been associated to higher mortality rate 55,56 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the myocarditis degree and HIF‐1α/CD73 expressions directly correlated with cardiac parasite load. These findings are consistent with works that report a positive correlation between the parasite persistence and the extension of inflammatory infiltrate in Chagas myocarditis 15,51,52,53,54 . Notably, Chagas patients have worse prognosis compared to cardiomyopathies from other etiologies and, in particular, male gender has been associated to higher mortality rate 55,56 .…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with works that report a positive correlation between the parasite persistence and the extension of inflammatory infiltrate in Chagas myocarditis. 15,51,52,53,54 Notably, Chagas patients have worse prognosis compared to cardiomyopathies from other etiologies and, in particular, male gender has been associated to higher mortality rate. 55,56 These studies suggest that, despite the limited parasite presence in cardiac tissue, the potential damage that can cause over time is comparable to the amount of local parasite load.…”
Section: Discussionmentioning
confidence: 99%
“…However, uncontrollable persistent IL-6 production has been associated in the development of various autoimmune and chronic inflammatory diseases and even cancers [ 14–17 ]. Many studies have shown that IL-6 has anti-parasite protective responses against some tissue parasites as Trypanosoma cruzi [ 18 , 19 ], Toxoplasma gondii [ 20 ], and Leishmania major [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Los anticuerpos de inmunoglobulina G circulantes (IgG) contra los receptores muscarínicos M2 (Auto AC M2) han sido asociados a la presencia de disautonomía temprana en pacientes con enfermedad chagásica crónica, con manifestaciones clínicas tales como bradicardia sinusal o anomalías en la conducción auriculoventricular. (5)(6)(7) Otra línea de investigación la constituye el estudio de los autoanticuerpos contra receptores β 1 y 2 que pueden ser producidos por los pacientes con miocardiopatía chagásica. (8) Estos autoanticuerpos, originalmente dirigidos contra el parásito, reconocerían indistintamente antígenos similares en el huésped, un fenómeno conocido como "mimetismo".…”
Section: Introduccionunclassified